2015
DOI: 10.1021/acs.organomet.5b00629
|View full text |Cite
|
Sign up to set email alerts
|

Development of N-Heterocyclic Carbene–Copper Complexes for 1,3-Halogen Migration

Abstract: A series of NHC−copper complexes was synthesized and their potential to catalyze 1,3-halogen migration explored. Increasing the steric bulk around the metal drastically improves the lifetime of NHC−CuH species and promotes 1,3-halogen migration of both 2-bromo-and 2-chlorostyrenes through transfer of an aryl halogen to a benzylic carbon with concomitant arene borylation. The NHC-based system displays a broad substrate scope with notable advantages over previously reported phosphine-based catalysts, including c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 53 publications
2
42
0
Order By: Relevance
“…[23] In conclusion, the very bulky ligand IPr** allows the first spectroscopic characterization of am onomeric copper hydride [(IPr**)CuH, 2], which is not isolable in the solid state, but is found to be in equilibrium in solution with its dimer [(IPr**)CuH] 2 3.T hese results support the hypothesis that copper hydride aggregates dissociate in solution. [12] On the other hand, our data suggest that silver hydrides do not have the tendencyt oa ggregate in the solid state;h owever, the labile nature of the silver-carbene bond, which is typically used in carbene transmetalation reactions, [24] makes them prone to dissociation in solution.…”
Section: Angewandte Chemiementioning
confidence: 75%
See 1 more Smart Citation
“…[23] In conclusion, the very bulky ligand IPr** allows the first spectroscopic characterization of am onomeric copper hydride [(IPr**)CuH, 2], which is not isolable in the solid state, but is found to be in equilibrium in solution with its dimer [(IPr**)CuH] 2 3.T hese results support the hypothesis that copper hydride aggregates dissociate in solution. [12] On the other hand, our data suggest that silver hydrides do not have the tendencyt oa ggregate in the solid state;h owever, the labile nature of the silver-carbene bond, which is typically used in carbene transmetalation reactions, [24] makes them prone to dissociation in solution.…”
Section: Angewandte Chemiementioning
confidence: 75%
“…[10,11] However,t he existence of an equilibrium between am ononuclear LCuH and its polynuclear form (LCuH) n has never been experimentally observed. [12] Fors ilver hydrides,i n2 010 Liu et al isolated cationic [Ag 8 (m 4 -H){Se 2 P(OR) 2 } 6 ] + clusters B containing Ag Ihydride bridges (Ag-m-H-Ag), [13] and in 2013 Sadighi et al described the dimeric silver hydride cation C. [14] Theo nly crystallographically characterized monomeric coinage metal hydrides are gold complexes, [15] complex D being the first ever reported. [16] Herein we report the unprecedented spectroscopic characterization of am onomeric LCuH complex, which is in equilibrium in solution with its dimer [LCuH] 2 ,aswell as the isolation and crystallographic characterization of the first monomeric LAgH complex.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been increasing interest in the synthesis and catalytic application of coinage metal hydrides (M=Cu, Ag, Au) . The majority of catalytic studies have focused on the in situ generation of terminal metal hydride complexes stabilized by N‐heterocyclic carbene (NHC) ligands . There is, however, a growing appreciation that species possessing three‐center, two‐electron M−H−M bonds may play a role in catalysis.…”
Section: Figurementioning
confidence: 99%
“…Notable improvements in 1,3‐halogen migration were achieved with bulky NHC ligands (IPent and IHept) with 2‐bromo‐ and 2‐chlorostyrenes as substrates …”
Section: Cuh‐catalyzed Functionalizationsmentioning
confidence: 99%
“…Notable improvements in 1,3-halogen migration were achieved with bulky NHC ligands (IPent and IHept) with 2-bromoand 2-chlorostyrenes as substrates. [36] Ta ntillo, Schomaker,a nd co-workersa lso studied the mechanism of this interesting transformation. [37] Experimental and computational studies revealed interesting mechanistic features of this process.I ts eems unlikely that the reaction involvesc hanges in the oxidation state of copper.…”
Section: Other Cuh-catalyzedreactionsmentioning
confidence: 99%